GM-CSF Down-Regulates TLR Expression via the Transcription Factor PU.1 in Human Monocytes. - Kambis Sadeghi; Lukas Wisgrill; Isabelle Wessely; Susanne C Diesner; Simone Schüller; Celia Dürr; Armando Heinle; Monika Sachet; Arnold Pollak; Elisabeth Förster-Waldl; Andreas Spittler (PLoS ONE, 2016)
Toll-like receptors (TLR) are crucial sensors of microbial agents such as bacterial or viral compounds. These receptors constitute key players in the induction of inflammation, e.g. in septic or chronic inflammatory diseases. Colony-stimulating factors (CSFs) such as granulocyte-macrophage-CSF (GM-CSF) or granulocyte-CSF (G-CSF) have been extensively investigated in their capacity to promote myelopoiesis in febrile neutropenia or to overcome immunosuppression in patients suffering from sepsis-associated neutropenia or from monocytic immunoincompetence. We report here that GM-CSF, downregulates TLR1, TLR2 and TLR4 in a time- and dose-dependent fashion in human monocytes. Diminished pathogen recognition receptor expression was accompanied by reduced downstream p38 and extracellular-signal-regulated kinase (ERK) signaling upon lipoteichoic acid (LTA) and lipopolysaccharide (LPS) binding-and accordingly led to impaired proinflammatory cytokine production. Knockdown experiments of the transcription factors PU.1 and VentX showed that GM-CSF driven effects on TLR regulation is entirely PU.1 but not VentX dependent. We further analysed monocyte TLR and CD14 expression upon exposure to the IMID® immunomodulatory drug Pomalidomide (CC-4047), a Thalidomide analogue known to downregulate PU.1. Indeed, Pomalidomide in part reversed the GM-CSF-mediated effects. Our data indicate a critical role of PU.1 in the regulation of TLR1, 2, 4 and of CD14, thus targeting PU.1 ultimately results in TLR modulation. The PU.1 mediated immunomodulatory properties of GM-CSF should be taken into consideration upon usage of GM-CSF in inflammatory or infection-related conditions.